“Validity of a scale of Latin American perception of fear and concern transmitted by the media during the pandemic (MED-LAT-COVID-19)“ - Garlisi-Torales, Luciana D. (2022)
“Introduction: The pandemic has caused fear, especially due to the daily disseminated news; however, there is not an instrument to measure this fear in multiple realities. Objective: To validate a scale for Latin American perception of fear and concern transmitted by the media during the pandemic. Methodology: This is an instrumental study. The survey was based on an instrument which was pre-validated in Peru and submitted to 15 experts in almost 10 countries. Subsequently, thousands of people were surveyed in 13 Latin American countries, whose answers were used for descriptive statistics for validation. Results: Confirmatory Factor Analysis (CFA) generated two re-specifications, where four items were eliminated from the original scale. With these changes, the global goodness of fit (absolute and incremental) were satisfactory (CFI ¼ 0.978; TLI ¼ 0.964; GFI ¼ 0.976; AGFI ¼ 0.949; RMSEA ¼ 0.075 and RMR ¼ 0.029). The first factor measures the media exaggeration (three questions); the second, the fear transmitted by the media (three questions); and the third, the fear transmitted by others different from the media (two questions). The Cronbach’s alpha coefficient was higher than 0.70 for the scale and its factors. Conclusion: The MED-LAT-COVID-19 scale reported a good adjustment. It has eight items in three factors, which could be measured in an isolated way, or along with other tests that assess mental health in the current pandemic context.“